Last ice sheet recession and landscape emergence above sea level in east-central Sweden, evaluated using in situ cosmogenic 14 C from quartz - B. W. Goodfellow; A. P. Stroeven; N. A. Lifton; J. Heyman; A. Lewerentz; K. Hippe; J.-O. Näslund; M. W. Caffee (Geochronology, 2024)
In situ cosmogenic 14 C (in situ 14 C) in quartz provides a recently developed tool to date exposure of bedrock surfaces of up to ∼ 25 000 years. From outcrops located in east-central Sweden, we tested the accuracy of in situ 14 C dating against (i) a relative sea level (RSL) curve constructed from radiocarbon dating of organic material in isolation basins and (ii) the timing of local deglaciation constructed from a clay varve chronology complemented with traditional radiocarbon dating. Five samples of granitoid bedrock were taken along an elevation transect extending southwestwards from the coast of the Baltic Sea near Forsmark. Because these samples derive from bedrock outcrops positioned below the highest postglacial shoreline, they target the timing of progressive landscape emergence above sea level. In contrast, in situ 14 C concentrations in an additional five samples taken from granitoid outcrops above the highest postglacial shoreline, located 100 km west of Forsmark, should reflect local deglaciation ages. The 10 in situ 14 C measurements provide robust age constraints that, within uncertainties, compare favourably with the RSL curve and the local deglaciation chronology. These data demonstrate the utility of in situ 14 C to accurately date ice sheet deglaciation, and durations of postglacial exposure, in regions where cosmogenic 10 Be and 26 Al routinely return complex exposure results.